THE ROLE OF STATE PROGRAMS IN THE DEVELOPMENT OF ENERGY INFRASTRUCTURE (Economics and region, 2025)
THE ROLE OF STATE PROGRAMS IN THE DEVELOPMENT OF ENERGY INFRASTRUCTURE
Keywords: State Programs; energy; infrastructure; sustainable development; government; energy sector; energy sources; renewable energy